An introduction to motivational interviewing. Issue 2 (March 2022) - Gary, Annette; Kiper, Valerie; Geist, Rebecca
Abstract : Nurses can use this tool for change in a variety of situations to help patients learn to live healthier lives. Abstract : Nurses can use this tool for change in a variety of situations to help patients learn to live healthier lives.